The Effectiveness of Law Enforcement on Cybercrime: A Case Study of Online Fraud in South Sulawesi - Syahfallah, Zulfan Akbar; Razak, Askari; Salle, Salle (CV. Social Politic Genius (SIGn), 2025)
The escalation of cyber fraud offenses within the South Sulawesi Regional Police’s jurisdiction poses serious challenges for law enforcement authorities, particularly given the limitations of conventional regulatory instruments that fail to address the characteristics of digital crime. This research aims to conduct an in-depth analysis of law enforcement disparity triggered by the normative gap between the application of Article 378 of Law Number 1 of 1946 and Law Number 11 of 2008 and its amendments, evaluate structural and cultural obstacles distorting investigation effectiveness, and project a systemic solution through the transition to Law Number 1 of 2023. Employing a socio-legal research method with a qualitative approach, this study integrates doctrinal analysis with empirical data obtained through in-depth interviews with investigators, judges, and victims. The results reveal crucial facts regarding regulatory disharmony, where law enforcement officials experience inertia in exercising their authority to cut off digital access due to unprepared forensic infrastructure at the regional level and low public legal literacy. This phenomenon creates a paradox of blunt law enforcement and perpetuates disparities in court verdicts. In conclusion, this study asserts that partial reform is no longer adequate to address the complexity of cybercrime. The study’s implications include concrete steps, such as formulating standard operating procedures aligned with Article 493 of Law Number 1 of 2023, forensic laboratory decentralization, and adopting internet access rights revocation sanctions as a futuristic sentencing strategy that guarantees legal certainty and restorative justice.